Psychological Analysis of Games Citizens Play - Petrovska, Inha (Journal of Education Culture and Society, 2023)
Aim. The research aim is to present the most common games citizens play, a description of the main game theses and roles, psychological gains and rewards, paradigms of relations between the citizen and the state, which determine the emergence of the game, as well as opportunities to quit the game.Methods. To achieve the goal, a system of general scientific methods was used: analysis and generalisation of the main provisions of source studies regarding citizenship and the social role of the citizen, systematisation and generalisation of scientific provisions about games, as well as methodological provisions of Berne's transactional analysis.Results. 43% of Ukrainian citizens engage in "game" interaction with the state. The most common games citizens play are: "Persecution" ("The state oppresses me"), "Offended" ("If it wasn’t for this state…"), "Parasite" ("The state owes me and should keep me"), "Patriot" ("Only I love Ukraine, all others are traitors"), "Exemplary citizen" ("I perform my civic duties better than anyone").Conclusions. Implementation of the role of a Citizen can lead to both constructive relations with the state and surrogate relations, which lead to various psychological games-manipulations. The developed system of psychological consulting practices for the prevention of civic identity "game" deformations can be used in the process of psychological support of civic identity formation in the development of complex training, and corrective activities, as well as in the educational process when creating programs of civic education and the development of civic competencies.